The Influence of Service Quality and College Image on Student Satisfaction and Its Implications for Student Loyalty - Harahap, Linda Rahmadhani; Djogo, Y.Ony; Redjeki, Finny (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the influence of Service Quality and College Image on Student Satisfaction and its implications on Loyalty at the Bangkinang Riau College of Economics. The background of this study is based on the decline in the number of students every year and poor service quality which is suspected to reduce student loyalty. The method used is quantitative with a descriptive and verification approach. The number of respondents was 177 people who were determined by the Slovin technique. The data analysis technique used path analysis to test the direct and indirect relationships between variables. The results showed that Service Quality and College Image had a significant effect on Performance, with coefficients of 0.496 and 0.416, respectively. Student Satisfaction also had a significant effect on Loyalty with a coefficient of 0.784. In addition, the indirect effect of Service Quality on Loyalty through Student Satisfaction was 0.708, while the direct effect was only 0.502. The total contribution of the model to the Loyalty variable was 90.4% (R² = 0.904). The conclusion of this study is that service quality and the image of the college play a significant role in increasing student satisfaction and loyalty. Therefore, it is necessary to improve the image of the Bangkinang College of Economics.